E-commerce : business, technology, society - Laudon, Kenneth C.; Traver, Carol Guercio (Boston : Pearson/Addison Wesley, 2004)
The book introduces students to the concepts and practice of electronic commerce.it emphasizes the tree major forces behind e-commerce: business fundamentals, technology opportunities, and social issues.
Includes bibliographical references and index.
Keywords: Electronic commerce; Internet marketing; Information technology